2000
DOI: 10.1002/cd.23220008804
|View full text |Cite
|
Sign up to set email alerts
|

Pages from a sociometric notebook: An analysis of nomination and rating scale measures of acceptance, rejection, and social preference

Abstract: Sociometry has had a prominent place in the research literature on children's social development. It has been used widely in the study of peer relations as both a technique for measuring the positive and negative forces among children and as a conceptual scheme for understanding the basic processes of the peer system. Beginning with Moreno's landmark publications (for example, Moreno, 1934), sociometry has been used by social developmentalists interested in peer relations as a powerful empirical and conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
11

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 8 publications
3
73
1
11
Order By: Relevance
“…Certainly, ratings ensure that all participating classmates are considered, whereas nominations depend to a greater extent on children's ability to remember and identify classmates who are most salient for liking and disliking. Although ratings are often used to derive a mean score reflecting the average level of acceptance by peers, the end points can be validly used as equivalents to liked-most and liked-least nominations (Bukowski, Sippola, Hoza, and Newcomb, 2000). Using the lowest rating of likability ("not at all") as a means to identify mutual dislike would have the advantage of providing the opportunity for more than three mutual dislike relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, ratings ensure that all participating classmates are considered, whereas nominations depend to a greater extent on children's ability to remember and identify classmates who are most salient for liking and disliking. Although ratings are often used to derive a mean score reflecting the average level of acceptance by peers, the end points can be validly used as equivalents to liked-most and liked-least nominations (Bukowski, Sippola, Hoza, and Newcomb, 2000). Using the lowest rating of likability ("not at all") as a means to identify mutual dislike would have the advantage of providing the opportunity for more than three mutual dislike relationships.…”
Section: Resultsmentioning
confidence: 99%
“…However, research in the 1960s and 1970s showed that they were only modestly (negatively) correlated or orthogonal and were associated with different behaviors (see Hymel et al, 2002 ), laying the foundation for classifi cation schemes that treated acceptance and rejection as separate dimensions able to distinguish accepted, rejected, neglected, and controversial children (e.g., Coie et al, 1982 ;Gronlund, 1959 ;Maassen et al, 1997Maassen et al, , 2000. Subsequently, Bukowski, Sippola, Hoza, and Newcomb (2000) showed that the relationship between acceptance and rejection is both linear (and negative) and curvilinear. Thus, children who are highly accepted are typically low in rejection, although poorly accepted children may vary in their level of rejection.…”
Section: Methodological Issues In Assessing Peer Acceptance and Rejecmentioning
confidence: 99%
“…The concepts ''acceptance'' and ''rejection'', traditionally regarded as separate dimensions [e.g. Bukowski et al, 2000], come into play at group level. A computer program is available to split the rating scale into two halves and to calculate the sums of the ratings on the positive and negative halves.…”
Section: Methodsmentioning
confidence: 99%